2017
DOI: 10.18203/2349-3291.ijcp20172668
|View full text |Cite
|
Sign up to set email alerts
|

The effects on carotid artery intima-media wall thickness and development of atherosclerosis in children on anti-epileptic drug monotherapy

Abstract: Background: Children with seizure disorder and requiring long-term anti-epileptic drugs are predisposed for development of atherosclerosis. We monitored the carotid artery intima wall thickness of the children on Antiepileptic drug monotherapy along with their lipid profile for a period of one year. Methods: Children under 18 years, who were newly diagnosed with epilepsy or were already on anti-epileptic drug monotherapy were included in the study period of one year. They were then prospectively followed-up at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…32 Contrary to our findings, Ksoo et al reported that CIMT was not significantly increased in patients receiving CBZ and VPA compared to controls. 25 In our study, we reported significant changes in lipid profile including TC, TG, LDL, HDL, and Apo A1 in children with epilepsy who received valproate and carbamazepine compared to levetiracetam and controls. Our results are consistent with previous studies that reported dyslipidemia with long-term AED therapy with elevation in the serum levels of TC and LDL.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…32 Contrary to our findings, Ksoo et al reported that CIMT was not significantly increased in patients receiving CBZ and VPA compared to controls. 25 In our study, we reported significant changes in lipid profile including TC, TG, LDL, HDL, and Apo A1 in children with epilepsy who received valproate and carbamazepine compared to levetiracetam and controls. Our results are consistent with previous studies that reported dyslipidemia with long-term AED therapy with elevation in the serum levels of TC and LDL.…”
Section: Discussionmentioning
confidence: 52%
“…The gender distribution and clinical characteristics of our patients were comparable to other studies. 4,25 Our study showed the difference in BMI between cases and controls was not statistically significant (P >.05). Contrary to our results, El-Farahaty et al, found a significantly higher BMI among cases receiving valproate and levetiracetam compared to controls (P = .003).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…CIMT was significantly higher in patients receiving multidrug and valproate compared to the control group, with no difference in the LEV group. Ksoo et al 33 illustrated a significant increase in CIMT values in children receiving PHT and CBZ after 3 months of therapy. Recent studies showed that patients with epilepsy who received AEDs might exhibit an increased risk of myocardial infarction, stroke, and cardiovascular death that may be triggered by affecting ADMA and homocysteine concentration and serum lipid levels.…”
Section: Discussionmentioning
confidence: 97%
“…Chronic exposure to these drugs can disturb the oxidative balance, triggering oxidative stress. This condition will lead to endothelial cells damage, which in turn causes atherosclerosis [4], [6], [7]. As a result, the mortality rate increases which is associated with cardiovascular risk in epileptic patients who receive long-term therapy.…”
Section: Introductionmentioning
confidence: 99%